Trifluoroacetic Acid as an Efficient Catalyst for the Room Temperature Synthesis of 2-Aryl-1-arylmethyl-1H-1,3-benzimidazoles in Aqueous Media - Mohammad R. Mohammadizadeh; S. Zeinakhatoun Taghavi (E-Journal of Chemistry)
Trifluoroacetic acid (TFA) is introduced as a commercially available, inexpensive and effective catalyst for the selective and eco-compatible synthesis of 2-aryl-1-arylmethyl-1H-1,3-benzimidazoles via condensation reaction of o-phenylenediamine derivatives and aromatic aldehydes in ethanol/water at room temperature.